2017
DOI: 10.1039/c6ra25088b
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of physicochemical and functional properties of silver carp myofibrillar protein glycated with glucose and maltodextrin

Abstract: Myofibrillar protein (Mf) from silver carp (Hypophthalmichthys molitrix) was incubated with glucose and maltodextrin for 0–96 h at 50 °C and 75% relative humidity to obtain glycoconjugates in different periods of the Maillard reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The coating helps to stabilize the droplets from aggregation and coalescence and may also help reduce oxidation. Moreover, the emulsion stabilizing ability of food proteins could be improved following glycation (Maillard reaction), which has been widely reported. Regarding structural changes during glycation, food proteins can undergo gradual changes in total SH content, surface hydrophobicity, and conformation, which renders proteins more flexible and enhances steric hindrance . These changes improve the emulsifying ability of food proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The coating helps to stabilize the droplets from aggregation and coalescence and may also help reduce oxidation. Moreover, the emulsion stabilizing ability of food proteins could be improved following glycation (Maillard reaction), which has been widely reported. Regarding structural changes during glycation, food proteins can undergo gradual changes in total SH content, surface hydrophobicity, and conformation, which renders proteins more flexible and enhances steric hindrance . These changes improve the emulsifying ability of food proteins.…”
Section: Introductionmentioning
confidence: 99%
“…As the unreacted glucose was removed after glycation, the MRPs were re-dissolved in 0.5 M NaCl containing 40 mM Tris-HCl (pH 7.5). The amount of glucose bound to MF was determined by the phenol-sulphuric acid method (Liu et al, 2017a(Liu et al, , 2017b.…”
Section: Bound Glucose To Mfmentioning
confidence: 99%
“…Silver carp ( Hypophthalmichthys molitrix ) is a major freshwater fish, where myofibrillar protein (MF) constitutes about 60% of the total protein and serves as important functional component (Liu et al ., 2016). Many studies have found that glycation of silver carp MF via MR could effectively tune protein emulsifying properties (Liu et al ., 2017a), gel‐forming ability (You et al ., 2012), solubility (Liu et al ., 2019), and thermal stability (Liu et al ., 2016). In the present study, the ‘dry’ glycation of silver carp MF with glucose was systematically investigated to explore the physicochemical properties, the loss of Lys and Arg, and the formation of corresponding AGEs in resultant glycoconjugates.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, glycation has been exploited to improve the solubility and emulsifying properties of MPs since the very beginning of this industry (Saeki, 1997; Saeki & Inoue, 1997). Generally, saccharides with smaller molecules showed faster reaction rates (Liu et al., 2017a).…”
Section: Glycation and Glycosylationmentioning
confidence: 99%
“…Glycation of konjac oligo‐glucomannan (KOG) with silver carp myofibrils and myosin was examined in several studies. The functionalities of MP‐KOG conjugates, including solubility and emulsion activity, reached a maximum after 8 to 12 hr dry‐heating glycation, while longer incubation periods might result in thermal denaturation (Liu et al., 2017a). Similarly, glycation with KOG also increased the emulsion properties of silver carp myosin by increasing the flexibility and steric hindrance of proteins (Liu et al., 2017b).…”
Section: Glycation and Glycosylationmentioning
confidence: 99%